SUITABILITY ANALYSIS OF PEDESTRIAN WAYS WITH THE ACTIVE LIVING STREET CONCEPT APPROACH - Arsita, Puput Dewi; Jordan, Nadia Almira (Border: Jurnal Arsitektur, 2022)
Kampung Pelajar is an educational area that causes travel attractions on the surrounding roads so there is a tendency to experience traffic density during daytime and night. Today the implementation of the government zoning system in education has encouraged equal access to educational services through a student admission system that considers the distance from home to the school. The implementation of this system has an impact on reducing loading on roads that have indications of high density due to student movement during rush hour. Based on initial observations, walking on pedestrian paths tend to be less when compared to vehicle. This phenomenon causes a decrease in the number of pedestrians because the function of the pathway is not optimal. This research aims to evaluate the pedestrian way suitability with the Active Living Street concept, by Mapping analysis with comparative description. The research results showed that based on the examination of four existing segmented routes, the majority of pedestrian way elements are not meet the criteria, such as obstacle, type of pavement, route dimension, signage and road marking, seatings, bollard, and safety barrier.